Interdependency versus Notions of Decoupling in a Globalising World: Assessing the Impact of Global Economics on Industrial Developments and Inter-Ethnic Relations in Penang, Malaysia - Michael Jacobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2010)
Due to the increasingly integration and thus inter-dependency between the global economy, a given national economy and their societal embedment a triangulation between the three elements is a must if one is to understand the dynamic processes between them. This article focuses especially on the national economic and societal aspects of such a triangulation thus positioning the national dependencies of the global economy in the background. The notion of triangulation is perceived by the author to be more holistic and relational oriented compared to an approach based on decoupling. The latter aims through sector defined studies to assess the level of connectivity between global and national economics as well as between them and their societal embedment in order to detect whether there are potential fault-lines between the three thus mitigating the notion of decoupling. This article applies a triangular approach on the electronic and electrical manufacturing sector in Penang. It concentrates in particular on how companies within this sector relate to pertinent governmental initiated industry policies and the impact of the inter-ethnic related affirmative action policy in this connection. The global aspect of the triangulation has thus been put on a back burner in this study, as the article emphasises the importance of pointing towards the inter-dependency between the political, the inter-ethnic and the economic sectors in Penang, as they are perceived to condition each other.
hdl:10398/8203
Keywords: 330; Entwicklung; Industrialisierung; Ethnische Beziehungen; Malaysia